International Refugees Protection in the Context of Human Rights - Supriadi, Slamet (Law Research Review Quarterly, 2021)
Refugees are defined as people who are due to a reasonable fear of persecution, caused by reasons of race, religion, nationality, membership in certain social groups and political parties, are outside their nationality, and do not want protection from the country. When refugees leave their home country or residence, they leave their lives, homes, possessions, and family. The refugees cannot be protected by their home country because they are forced to leave their country. Therefore, protection and assistance to them is the responsibility of the international community. In countries receiving refugees, they often experience inhumane treatment such as rape, assault, discrimination, repatriation by force, which lead to the violation of human rights. There has been regulation for human rights in refugee issues both internationally and regionally, for instance, the Convention related to Status of Refugee 1951 and The Protocol relating to the Status of Refugee 1967. There are at least five basic rights of refugees, they are the right to be protected from returning to the country of origin forcibly (non-refoulement), the right to seek asylum, the right to obtain equality and non-discrimination, the right to live, and to be secured, as well as the right to return home.